Penerapan Metode Elgamal Untuk Mengamankan Teks Pada File Dokumen Word - Abdul Halim Hasugian; Raissa Amanda Putri; Annisa Shafira Zuhri (STMIK Budi Darma, 2023)
Text that contains a lot of characters always causes problems with storage media and time speed during data transmission. Text files are files that contain information in text form. data originating from word processing documents, numbers used in calculations, names and addresses in databases are examples of input text data consisting of characters, numbers and punctuation marks. The problem is that if the text file contains important information and is stolen, the thief can exploit the stolen data into profitable information and if the data is damaged then the data owner suffers a loss. therefore it is necessary to apply security to text files. This research uses the Elgamal method for security of important text files. with security using the elgamal method, important text files have good security. This algorithm is based on the discrete logarithm problem on the group ?P*. The ElGamal algorithm consists of three processes, namely the key formation process, the encryption process and the decryption process. This algorithm is a block cipher, which carries out an encryption process on plaintext blocks and produces ciphertext blocks which are then decrypted, and the results are combined back into a complete and comprehensible message. As a result of the research, it can be concluded that implementing a secret message application can secure Microsoft Word files. The result is that this application is very useful for securing documents so that their contents are not known by unauthorized people. This program produces applications using steps and formulas from the Elgamal algorithm, then changes the text content in the Microsoft Word file as input, then the Elgamal algorithm can be applied and turned into unknown codes (ciphertext). By using Visual Basic 2012 programming and then applying the algorithm or stages of Elgamal, it can result in the application of the Elgamal Method for Securing Microsoft Word Files